LARANGAN PEMILIKAN TANAH ABSENTEE BERDASARKAN UUPA NO. 5 TAHUN 1960 - SANIAH . (JURNAL ILMIAH SIMANTEK, 2022)
UUPA No. 5 of 1960 and its implementing regulations prohibit a person or legal entity from owning and controllingagricultural land on an absentee basis because arable land becomes inefficient. After all, the landowner does not reside inthe sub district where the land is located. However, the progress of communication and transportation facilities has been sorapid at this time that the prohibition of absentee land ownership is irrelevant. What is needed is to think about andreformulate the absentee land arrangement.